2020
DOI: 10.7759/cureus.12047
|View full text |Cite
|
Sign up to set email alerts
|

Personal Protective Equipment and Headaches: Cross-Sectional Study Among Moroccan Healthcare Workers During COVID-19 Pandemic

Abstract: BackgroundHealthcare workers in frontline during the coronavirus 19 disease (COVID-19) pandemic are mandated to wear specific personal protective equipment (PPE) including high filtrating masks and/or eye protection during extended period of time. Compressive headaches secondary to PPE use including N95 masks have been reported. We aim to describe subtypes of headache related to PPE use in our hospital in Casablanca and working condition factors associated with it. MethodsWe conducted a cross-sectional study a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(54 citation statements)
references
References 19 publications
7
47
0
Order By: Relevance
“…Since the start of COVID-19 in December 2019, there have been a total of 6 published studies specifically conducted to understand PPE-associated headache amongst healthcare workers (see Table 1 ) [ 25 ••, 33 •, 34 •, 35 •, 36 •, 38 •]. Based on these studies, several factors have been found to confer a greater likelihood of developing de novo PPE-associated headaches.…”
Section: Epidemiologymentioning
confidence: 99%
See 4 more Smart Citations
“…Since the start of COVID-19 in December 2019, there have been a total of 6 published studies specifically conducted to understand PPE-associated headache amongst healthcare workers (see Table 1 ) [ 25 ••, 33 •, 34 •, 35 •, 36 •, 38 •]. Based on these studies, several factors have been found to confer a greater likelihood of developing de novo PPE-associated headaches.…”
Section: Epidemiologymentioning
confidence: 99%
“…These include having a pre-existing primary headache diagnosis (e.g. migraine or tension-type headache) [ 25 ••, 34 •], engaging in shift-work lasting more than 8 h [ 38 •] or up to 12 h [ 23 , 38 •] at a stretch, and the use of a filter mask (as opposed to a surgical mask) [ 35 •]. The combined usage of PPE (N95 respirator and protective eyewear) for >4 h per day [ 25 ••] or the use being a healthcare worker (in particular being a nurse) or having a history of asthma was also found to correlate with the development of such headaches.…”
Section: Epidemiologymentioning
confidence: 99%
See 3 more Smart Citations